2017
DOI: 10.1371/journal.pone.0174734
|View full text |Cite
|
Sign up to set email alerts
|

MRI-detection rate and incidence of lumbar bleeding sources in 190 patients with non-aneurysmal SAH

Abstract: BackgroundUp to 15% of all spontaneous subarachnoid hemorrhages (SAH) have a non-aneurysmal SAH (NASAH). The evaluation of SAH patients with negative digital subtraction angiography (DSA) is sometimes a diagnostic challenge. Our goal in this study was to reassess the yield of standard MR-imaging of the complete spinal axis to rule out spinal bleeding sources in patients with NASAH.MethodsWe retrospectively analyzed the spinal MRI findings in 190 patients with spontaneous NASAH, containing perimesencephalic (PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…These methods are minimally invasive or noninvasive, time-saving, and lowcost and produce high-quality images. However, the clinical effects reported in some studies are quite different [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…These methods are minimally invasive or noninvasive, time-saving, and lowcost and produce high-quality images. However, the clinical effects reported in some studies are quite different [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…We report a spinal bleeding source in 2.86% of patients with AN-SAH. Kashefiolasl et al [27] reported an MRI detection rate and incidence of lumbar bleeding sources of 1.05% among 190 patients with AN-SAH. Some authors have reported a spinal tumor as the bleeding source [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…The detection rate increased by up to 25% in cases where patients with radicular sciatic pain at the presentation of symptoms received an MRI. The study concluded that routine radiological investigation of the spine in every NASAH patient is not recommended due to the rarity of the pathology and should be done as symptom orientated ( 7 ). Similar findings were also noted in five other studies investigating NASAH via MRI spine to locate the source of bleeding; they report only a 1% positive finding ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial SAHs caused by spine vascular abnormalities are extremely rare. In a literature search, only five studies were found published in the past decade (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%